Peer Effects in Employment Status: Evidence from Housing Lotteries for Forced Evacuees in Fukushima - Ayako Kondo; Masahiro Shoji (Institute for the Study of Labor (IZA), 2016)
Does a high peer employment rate increase individual employment probability? We exploit the random assignment of temporary housing to evacuees from the Fukushima Daiichi nuclear power plant accident to identify the effect of neighbors' employment rates on an individual's probability of finding a job post-evacuation. Using unique survey data collected in 14 clusters of temporary housing 2.5 years after the accident, we find a significantly positive peer effect: a one standard deviation increase in the initial employment rate of an individual's peers makes the hazard of restarting work 1.53 times larger during the six months after housing move-in.
Keywords: J20; J64; 330; peer effect; neighborhood effect